Bobot telur, indeks bentuk telur, dan nilai kantung udara telur itik pengging setelah pemberian imbuhan tepung daun kelor (Moringa oleifera Lam.) dalam pakan - Novia Marcelina; Muhammad Anwar Djaelani; Sunarno Sunarno; Kasiyati Kasiyati (Jurnal Biologi Tropika, 2020)
Moringa oleifera leaves contain nutrition of protein, lipid, carbohydrate, fiber, calcium, phosphorus as well as bioactive content such as tannin and saponin, that have the potential to improve egg quality. The objective of this research to evaluate the effect of Moringa powder of weight, shape index, and air space value of Pengging duck eggs. The study used a completely randomized design (CRD) consisting of 5 treatments with four replication, i.e., K0 (100% basal feed without Moringa leaves powder), K1 (basal feed and 2.5% Moringa leaves powder), K2 (basal feed and Moringa leaves powder), K3 (basal feed and 7.5% Moringa leaves powder) and K4 (basal feed and 10% Moringa leaves powder). The data were obtained  from a total of 60 female Pengging duck of 28 weeks old or sexually mature. Feed treatments administrated for six weeks started in 26 to 32 weeks old ducks. The measurement of research variables was carried out every week and measured for three weeks. The data of the study were analyzed by one way-ANOVA at a significant difference level of  5%. The results showed that the addition of Moringa leaves powder did not a significant difference (P > 0.05) in weight, shape index, and air space value of pengging duck eggs. Overall concluded that the addition of Moringa leaves powder with a concentration of 2.5; 5; 7.5; dan 10% in Pengging duck feed could not change egg quality.